The The Bioceanic Route and public policies of the border cities of Porto Murtinho/Brazil – Carmelo Peralta/Paraguay - Pinho de Almeida, Luciane (2021)
With the arrival of the Bioceanic Route on the border of the municipalities of Porto Murtinho (Brazil) and Carmelo Peralta (Paraguay), the forecast is that social changes will take place regarding the structure of the municipalities and their daily lives. This article aims to present reflections on the issues that permeate public policies on the border, specifically the municipalities of Porto Murtinho and Carmelo Peralta. This work is the result of the development of studies for the preparation of the Master Plan for the city of Porto Murtinho, data were collected between September 2020 and June 2021 through interviews with public managers of the municipality, questionnaires applied with the local population, as well. as it involved bibliographic and documentary research that help guide new paths for local policies. From the data collected, it is observed that currently the municipality of Porto Murtinho has public facilities capable of serving the population, considering its size. However, in view of the increase in the flow of people and the possible expected increase in its population, public policies must be in line with such development. In addition, in the city of Carmelo Peralta, the precariousness of public services is evident, especially in health and social assistance. Currently, many Paraguayans already use services on the Brazilian side of the border because they cannot access their place of origin. Thus, it is extremely important that public policies consider the particularities of a border municipality that is about to go through a moment of great development, demanding dialogue and bilateral agreements that aim to guarantee the social rights of local populations.